A Comprehensive Approach to Ending Bullying in Indonesia's Medical Residency Programs: A Policy Brief - Pujiwati Permata Rima, Siti; Bumantari, Annisa Fitri; Nabillah, Bayuni Izzat; Malufti, Chandrika Najwa; Adhiguna, Gunawan; Hadianto, Henry; Kakisina, Jurika; Ikhromi, Noryanto; Amalia, Nur Izzaty; Fathana, rezka dwi; Jaehan, Risa; Putri, stefanie karina; Setiawan, Yosia Putra (Acta Neurologica Indonesia, 2024)
Bullying is a pervasive issue in medical education and practice, affecting educators, residents, nurses, and students. In Indonesia, it has emerged as a significant concern, particularly within medical residency programs. Often described as a chronic problem, bullying in medicine negatively impacts patient care and is difficult to eradicate. It occurs both in professional settings and through digital platforms like WhatsApp and Telegram. Bullying in medical education takes various forms, including physical and non-physical, and often escapes the attention of faculty, universities, teaching hospitals, and victims' families. These acts, typically carried out by senior students in an organized manner, may be falsely perceived as part of the mentoring process, masking the harmful behavior.1